2021
DOI: 10.1136/bcr-2020-239932
|View full text |Cite
|
Sign up to set email alerts
|

Cat scratch disease sepsis in an immunocompromised patient

Abstract: As a greater number of households have pets, the likelihood of zoonotic infections can rise too. Although in most healthy individuals these infections are self-limiting, they are more serious and can lead to adverse outcomes in the immunocompromised. There is minimal information available for the immunocompromised patient who are pet owners or on pet handling. We report a case of cat scratch disease-related sepsis in an immunocompromised patient. This case illustrates the need for a detailed history, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Living with animals has demonstrated benefcial efects in children with chronic medical conditions [1][2][3]; for immunocompromised patients, however, the risk-beneft balance should be discussed individually, as should measures to prevent infections [4]. Although several cases of severe infections in immunocompromised patients transmitted by pets have been documented [8][9][10][11][12], it is unclear to what extent the risk of acquiring infections is increased in this population. Recent studies addressing colonization have reported signifcant rates of parasites, pathogenic bacteria, or multidrugresistant microorganisms colonizing pets, and many arthropods, which are potential vectors of infection, are common to humans and pets [9,28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Living with animals has demonstrated benefcial efects in children with chronic medical conditions [1][2][3]; for immunocompromised patients, however, the risk-beneft balance should be discussed individually, as should measures to prevent infections [4]. Although several cases of severe infections in immunocompromised patients transmitted by pets have been documented [8][9][10][11][12], it is unclear to what extent the risk of acquiring infections is increased in this population. Recent studies addressing colonization have reported signifcant rates of parasites, pathogenic bacteria, or multidrugresistant microorganisms colonizing pets, and many arthropods, which are potential vectors of infection, are common to humans and pets [9,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are considerable biases in the published literature. Cases of zoonosis transmitted from pets to immunocompromised patients have been reported [8][9][10][11][12] although few studies have determined precisely what proportion of human disease is attributable to pets [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of zoonoses in immunocompromised patients is difficult to determine because cases are sporadic and not subject to disease notification [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Lothstein et al reported a 0.86% incidence of zoonoses in 10197 pediatric patients with acute leukemia and 1 death from Cryptosporidium [ 38 ].…”
Section: Statements and Discussionmentioning
confidence: 99%